2009
DOI: 10.1002/hbm.20676
|View full text |Cite
|
Sign up to set email alerts
|

Differential force scaling of fine‐graded power grip force in the sensorimotor network

Abstract: Force scaling in the sensorimotor network during generation and control of static or dynamic grip force has been the subject of many investigations in monkeys and human subjects. In human, the relationship between BOLD signal in cortical and subcortical regions and force still remains controversial. With respect to grip force, the modulation of the BOLD signal has been mostly studied for forces often reaching high levels while little attention has been given to the low range for which electrophysiological neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
80
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 84 publications
(113 citation statements)
references
References 84 publications
29
80
4
Order By: Relevance
“…The main effect of movement results (i.e., the 0th order effect) confirmed these findings; especially in lobule V. A recent meta analysis of the different types of gripping (i.e., power or precision) or different patterns (static or dynamic) showed that lobule V was involved in all these motor tasks [King et al, 2014]; suggesting that this lobule is involved in the basic aspects of motor control during gripping. Within the medial region of lobule V, a positive linear relationship between force levels and activation was detected in our study, in line with previous findings with both low force [Keisker et al, 2009] and higher force ranges [Spraker et al, 2012]. We speculate that this indicates an increased recruitment of neurons in motor regions at the highest forces.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The main effect of movement results (i.e., the 0th order effect) confirmed these findings; especially in lobule V. A recent meta analysis of the different types of gripping (i.e., power or precision) or different patterns (static or dynamic) showed that lobule V was involved in all these motor tasks [King et al, 2014]; suggesting that this lobule is involved in the basic aspects of motor control during gripping. Within the medial region of lobule V, a positive linear relationship between force levels and activation was detected in our study, in line with previous findings with both low force [Keisker et al, 2009] and higher force ranges [Spraker et al, 2012]. We speculate that this indicates an increased recruitment of neurons in motor regions at the highest forces.…”
Section: Discussionsupporting
confidence: 93%
“…One of the interesting findings of this study is the bilateral activation in lobule VI seen in the main effect of movement analysis; this is in line with previous GF studies [Halder et al, 2007; Kuhtz‐Buschbeck et al, 2008], although it has rarely been discussed or possibly not detected [Keisker et al, 2009]. Our data, however, not only shows a contralateral activation of lobule VI (as well as the more familiar ipsilateral one) but also shows that the activation pattern of lobule VI is not homogenous.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations